Teacher-Made Comic Strip: A Strategic Intervention Material in Teaching Fundamental Operations on Integers - Uy, Edison (JPAIR Multidisciplinary Research, 2018)
A relatively large share of students often struggles in learning fundamental operations on integers because they express general dislike to its context for it has numerous rules that lead to confusion. In this perspective, the study proposed a teacher-made comic strip entitled Numerolandia: The Chosen One as an alternative way to increase and strengthen students’ knowledge and understanding of the fundamental operations on integers. It aimed to investigate its effectiveness to the identified bottom 20 students (based on the latest average in mathematics) of Grade Seven section Amethyst of Pangdan National High School, Catbalogan City during S.Y. 2017-2018. Quasi-experimental research design with one group pre-test post-test design was used. Thus, the comic strip was given to the student-participants for them to read and answer all the activities provided in it, and two questionnaires were served: one was about the assessment on fundamental operations on integers, and another was about the extent of acceptance on the comic strip. Thus, it was found out that the comic strip was an effective way of improving students’ knowledge and skills as it showed a notable positive 7.7 increase in their scores when they were exposed to this intervention and as to the degree of acceptance, based on the given indicators the student participants agreed to accept it strongly. Therefore, it is recommended that Mathematics teachers should innovate their teaching styles and strategies to fortify the students’ learning process like the use of a comic strip.